Pembagian Hukum Islam yang Tetap dan yang Berubah (Tsawâbit wa Mutaghayyirât) - Irawan, Andhi; Jalaluddin, Jalaluddin; Azhari, Fathurrahman; Hamdi, Fahmi (PT. Sharia Journal and Education Center, 2024)
Abstract This study examines the division of Islamic law into immutable laws (tsawâbit) and changeable laws (mutaghayyirât) within the framework of Sharia. The article highlights the importance of understanding immutable laws as an unchanging foundation, while flexible laws should be interpreted and implemented according to the continuously evolving social and cultural dynamics. In the post-revelation era, the task of Muslims is to interpret and apply the revelation in the context of the modern and ever-changing society. The plurality of interpretations and the diversity of expressions in practicing Islam are considered inevitable and not erroneous as long as the methodology used is accountable. The concept of the